La smartness e la competitività della città resiliente sfide e minacce per le città del ventunesimo secolo - Gerardo Carpentieri (Smart City, Urban Planning for a Sustainable Future, 2020)
The numerous and complex economic, social and environmental challenges that will have to be faced in the coming decades in the context of the governance of urban and territorial transformations will require the use of new approaches, capable of orienting development in a socially, economically and environmentally sustainable way. The choices and initiatives for change must guarantee an adequate quality of life for citizens and favourable conditions for the development of economic and social activities. Among the challenges that cities will have to face in the coming years is that of urban population growth. Demographic projections foresee that in the coming decades there will be a further increase in world population which will mainly affect urban areas. These forecasts further underline the need to intervene above all in cities, in order to reduce the effects of the potential threats that can occur as a result of unexpected critical events, both anthropogenic and natural. In recent years, national and local governments have planned to invest significant economic resources in the development and implementation of strategies capable of addressing possible weaknesses in urban systems. In the context of the governance of urban transformations, one of the most commonly used approaches for improving the capacity of urban systems to respond to external stressors refers to the resilience paradigm, understood as the capacity of a system, community or society to resist, absorb, adapt and recover from the impacts of a calamitous event in a timely and efficient manner, including through the preservation and restoration of its essential basic structures and functions. The implementation of solutions aimed at improving urban resilience is essential to reduce the possible economic, social and environmental impacts owing to the critical events that can affect cities. Furthermore, the use of this approach can offer greater security both to citizens and for economic activities, both in ordinary conditions and emergencies. The satisfaction of this need has now become a fundamental element of the competition between different territorial contexts and in particular between cities. The most recent studies on urban competitiveness highlight how the issue of developing urban resilience has become an essential aspect when evaluating the competitive capabilities of various territorial contexts. The development and implementation of interventions aimed at making cities resilient cannot disregard the use of physical and functional smart solutions, which now constitute an essential support in improving the response capacity of cities and their components to internal and external stresses. Making a city resilient requires the implementation of complex infrastructural and organizational interventions which must take into account the multiplicity and dynamism of the urban components involved, and which therefore must make use of the most recent technologies, hardware and software. Taking action on urban resilience can also enable cities to achieve a better level of smartness. The in-depth analysis and considerations brought together in this work are part of this broad scientific debate. In particular, the purpose of this work is to investigate the issues related to the challenges that cities will have to face in the coming decades in order to ensure an adequate quality of life for citizens, highlighting how the use of a resilient approach can improve the response of these territorial contexts in the event of critical situations. The issues of territorial competitiveness and urban smartness are studied in detail in the context of a new scientific, technical and cultural way of thinking which takes resilience as its primary reference paradigm. This is in order to understand how far resilient development is able both to support the improvement of a city's ability to compete with other territorial contexts, and to favour the achievement of an adequate level of urban smartness. The aim is to develop a detailed and up-to-date scientific reference framework regarding the main needs and critical events faced by cities, and the need to promote the use of an approach aimed at improving urban resilience, in the context of dealing with the external and internal stresses and changes which affect these territorial contexts. In other words, the study illustrates the relationships that can be established between the development of the resilient city and, on the one hand, the ability of an urban system to compete with other territorial contexts, and on the other, the potential offered by the use of smart, physical and functional solutions in an urban setting.